2021
DOI: 10.47191/jefms/v4-i8-30
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tourism in Promoting Export Performance in Indonesia: Gravity Model Approach

Abstract: The tourism sector has the opportunity as a source of information regarding the demand preferences of foreign tourists for goods produced in tourist destination countries. The preference of foreign tourists in this study is measured by using the value of Indonesian exports of goods to the country of origin of tourists one year after their visits. The purpose of this study is to analyze the role of the tourism sector in increasing demand for exports of domestic goods by foreign tourists. To overcome the endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In A. Refiana study of Indonesian exports connection to tourist inflow was shown that the preferences of tourists from Malaysia, Singapore, China, Japan, and Australia for Indonesian products are mostly in "food and beverages (primary)" and "food and beverages (processed)", followed only then with "industrial commodities" and "consumer goods". These results conclude that inbound tourism can stimulate export performance in certain areas (Refiana, Purwono, 2021).…”
Section: Methodssupporting
confidence: 55%
“…In A. Refiana study of Indonesian exports connection to tourist inflow was shown that the preferences of tourists from Malaysia, Singapore, China, Japan, and Australia for Indonesian products are mostly in "food and beverages (primary)" and "food and beverages (processed)", followed only then with "industrial commodities" and "consumer goods". These results conclude that inbound tourism can stimulate export performance in certain areas (Refiana, Purwono, 2021).…”
Section: Methodssupporting
confidence: 55%